2021
DOI: 10.18332/tid/132547
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and methods of dual users to quit vaping: Survey findings from adults who use electronic and combustible cigarettes

Abstract: strategies used (i.e. methods) to quit ECs among adults who use both ECs and CCs. Discontinuing EC use is common among adult CC smokers who try using ECs 3-5. In a large national study of US adults, over half (56%) of current CC smokers who started using ECs later discontinued ECs 4 and findings were similar in a European cohort study with a two year follow-up 5. Much of the prior research on stopping ECs includes adults who tried and subsequently discontinued ECs in the absence of self-defined regular EC use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…There is growing evidence that e-cigarette users and dual users are seeking help to quit e-cigarette use, because of health concerns, including increased risk of harm from COVID-19, costs and concerns about the addictive potential of vaping. 23 27 Moreover, dual users were found to report similar levels of interest in quitting e-cigarettes as exclusive vapers 28 and more attempts to quit smoking than exclusive smokers. 29 However, our understanding of the process of vaping cessation and dual use cessation is very limited, and evidence-based guidelines for vaping cessation interventions are yet to be developed.…”
mentioning
confidence: 93%
“…There is growing evidence that e-cigarette users and dual users are seeking help to quit e-cigarette use, because of health concerns, including increased risk of harm from COVID-19, costs and concerns about the addictive potential of vaping. 23 27 Moreover, dual users were found to report similar levels of interest in quitting e-cigarettes as exclusive vapers 28 and more attempts to quit smoking than exclusive smokers. 29 However, our understanding of the process of vaping cessation and dual use cessation is very limited, and evidence-based guidelines for vaping cessation interventions are yet to be developed.…”
mentioning
confidence: 93%
“…In addition to increasing concerns about the potential health risks of vaping, growing interest in quitting vaping has also been linked to the experience of some adverse physical effects (e.g., dry mouth, cough), the rising cost of vaping, and the need to break dependence on vaping products [ 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have explored how e-cigarette users attempt to quit vaping, and what their quit experiences are like. A cross-sectional survey of dual e-cigarette and combustible cigarette users found that e-cigarette users had a lifetime median of five e-cigarette quit attempts, and that the most common methods used were cutting down (68%), advice from a doctor (28%), and quitting "cold turkey (24%)" [10]. Preliminary evidence suggests that the e-cigarette cessation experience may share some similarities with quitting conventional cigarettes.…”
Section: Introductionmentioning
confidence: 99%